Analisis Hukum Islam terhadap Praktik Zakat Hasil Panen Padi di Desa Sidang Kurnia Agung, Rawa Jitu Utara, Mesuji - Samsudin (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2025)
Zakat is one of the pillars of Islam that must be fulfilled by every Muslim, and its implementation must adhere to the requirements established in Islamic law. Agricultural products that reach the prescribed nishab are obligated to be tithed accordingly. However, in practice, the farming community in Mantingan Village, Rawa Jitu Utara District, Mesuji Regency, demonstrates limited understanding regarding agricultural zakat. This condition motivates the present study, which aims to examine the implementation of agricultural zakat and analyze it from the perspective of Islamic law. The purpose of this research is to identify how agricultural zakat is practiced in Mantingan Village and to assess the conformity of these practices with Islamic legal principles. This study employs a qualitative research design with a socio-juridical approach, focusing on real conditions in the community to uncover facts that lead to problem identification and resolution. The data consist of primary data collected from interviews with farmers and religious leaders, and secondary data obtained from the Qur'an, Hadith, journals, articles, and relevant literature. The findings indicate that the agricultural yield in Mantingan Village has reached the nishab level required for zakat obligation according to Islamic law. Nonetheless, farmers tend to determine and distribute zakat based on their own practices rather than adhering to established Islamic legal guidelines. From the perspective of Islamic law, zakat on agricultural produce in Mantingan Village is generally issued either annually or after each harvest, yet the amount given does not align with the prescribed rates stipulated for agricultural zakat.